DEVELOPING A DIAGNOSTIC COMPLEX FOR THE POSTTRAUMATIC EPILEPSY - Sanakulova Dilnavoz Abdugani kizi; Djurabekova Aziza Takhirovna (Scholar Express Journals, 2024)
The purpose of our study was to study clinical features and improve instrumental diagnostics in patients with post-traumatic epilepsy
Keywords: with post-traumatic epilepsy; method; treatment